Das Escolas Técnicas Federais aos Institutos Federais: a licenciatura em Física no campus Goiânia do IFG - Araújo, Weslei Silva de (2016)
In this paper we sought to understand how the Degree in Physics in IFG Goiânia campus is structured and what the perspective of teachers in the area, specifically in the implementation of degree in Physics, and forward the changes in the institution. The choice of this theme is due to the requirement stipulated by law 11.892 of December 29, 2008, the Federal Institutes of Education, Science and Technology, in offering undergraduate courses, especially in the areas of Science and Mathematics, despite its recognized expertise in professional education. Some research has dealt with the theme of the presence of the degrees in FIs, discussing the profile, the deployment and the challenges that they are consoli dated. However, here we seek teachers' perception of the process. Characterized as a qualitative study we used bibliographical research to survey the changes via legal documents in the institution, as well as research on the site e -MEC for recognizing the quantity of courses offered in this mode before and after the creation of the IFs. For analysis of the survey responses a nd interviews with teachers of Physical area of Goiânia the IFG campus, we used content analysis, according to Bardin (2002). It was identified as perceived by teachers who: (i) changes in the institution provided an expansion and internalization, even disorderly; (Ii) the change in the teaching profession and school mischaracterization with devaluation of technical education; (Iii) the course designed to meet the law, structure and operation in construction, has a focus on specific knowledge at the expense of teaching; (Iv) teachers work almost exclusively in the classroom, with little or no research and extension activities. These aspects lead to understand that there is still a lack of identity in I Fs after implantation of degrees and forward the changes in this institutions.